Pendampingan Kegiatan Menulis Karya Ilmiah bagi Dosen IAI Darul Ulum Asahan - Siregar, Muhammad Fuad Zaini (Ibrah : Jurnal Pengabdian Kepada Masyarakat, 2023)
This paper mentoring activity aims to provide understanding to participants to understand the meaning of scientific papers. This activity also aims to train participants in writing scientific papers. This qualitative research uses a case study design of scientific writing assistance. The focus is on providing guidance and support to IAIDU Asahan lecturers. The instruments used are lectures, discussions and training. Writing scientific papers requires a systematic approach starting from planning, writing objectives, to handling obstacles that may arise. This process involves awareness of writing habits, development of planning and focus skills, and the ability to overcome internal and external obstacles. By identifying and understanding barriers, writers can achieve higher quality scientific work and make a positive contribution to the academic world.